Crater Lake Apoyo revisited--population genetics of an emerging species flock. - Matthias F Geiger (Public Library of Science (PLoS), 2013)
The polytypic Nicaraguan Midas cichlids (Amphilophus cf. citrinellus) have been established as a model system for studying the mechanisms of speciation and patterns of diversification in allopatry and sympatry. The species assemblage in Crater Lake Apoyo has been accepted as a textbook example for sympatric speciation. Here, we present a first comprehensive data set of population genetic (mtDNA & AFLPs) proxies of species level differentiation for a representative set of individuals of all six endemic Amphilophus species occurring in Crater Lake Apoyo. AFLP genetic differentiation was partitioned into a neutral and non-neutral component based on outlier-loci detection approaches, and patterns of species divergence were explored with Bayesian clustering methods. Substantial levels of admixture between species were detected, indicating different levels of reproductive isolation between the six species. Analysis of neutral genetic variation revealed several A. zaliosus as being introgressed by an unknown contributor, hereby rendering the sympatrically evolving L. Apoyo flock polyphyletic. This is contrasted by the mtDNA analysis delivering a clear monophyly signal with Crater Lake Apoyo private haplotypes characterising all six described species, but also demonstrating different demographic histories as inferred from pairwise mismatch distributions.